Conversion of the chill susceptible fruit fly larva (Drosophila melanogaster) to a freeze tolerant organism - Koštál, Vladimír; Šimek, Petr; Zahradníčková, Helena; Cimlová, Jana; Štětina, Tomáš (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Among vertebrates, only a few species of amphibians and reptiles tolerate the formation of ice crystals in their body fluids. Freeze tolerance is much more widespread in invertebrates, especially in overwintering insects. Evolutionary adaptations for freeze tolerance are considered to be highly complex. Here we show that surprisingly simple laboratory manipulations can change the chill susceptible insect to the freeze tolerant one. Larvae of Drosophila melanogaster, a fruit fly of tropical origin with a weak innate capacity to tolerate mild chilling, can survive when approximately 50% of their body water freezes. To achieve this goal, synergy of two fundamental prerequisites is required: (i) shutdown of larval development by exposing larvae to low temperatures (dormancy) and (ii) incorporating the free amino acid proline in tissues by feeding larvae a proline-augmented diet (cryopreservation).
Keywords: kryoprotektivní látky; krystalizace; Drosophila melanogaster; zmrazování; Diet; Proline; Freezing; larva; Adaptation, Physiological; Cryoprotective Agents; Crystallization; zvířata; Body Water; tělesná voda; Ice; Metamorphosis, Biological; biologická proměna; dieta; fyziologická adaptace; Larva; Animals; prolin; led